Appearances of Psychological Burnout in Football Players During Sports Training - A field Study on the Sports Union of the Municipality of Timgad - Rezig, Hafsa; Soltani, Asma (Milev Journal of Research and Studies, 2019)
At the present time, the phenomenon of psychological Burnout has attracted the attention of many researchers in the field of sports due to its negative effects on the achievements of athletes in the field of training and competition, where the frequent failure in tournaments and failure to achieve the desired goals into a state of psychological Burnout that leads the athlete to completely or partially away from exercise Training is the result of situations of negative emotional feeling. Therefore, this study aims to identify the indicators of psychological burning of football players during exercise. All 30 individuals in the study were selected to apply the psychosocial combustion index questionnaire, which was constructed by the two researchers.